EFFECTIVENESS OF PROJECT-BASED LEARNING AND 5E LEARNING CYCLE INSTRUCTIONAL MODELS - Kijambu John Baptist; D. N. Utami; Bambang Subali; S. Aloysius (Jurnal Kependidikan, 2020)
This study was aimed at determining and comparing the effectiveness of project-based learning and 5E learning cycle instructional models in improving the acquisition of new biological knowledge related to the human immune system. This quasi experiment study with a pretest-posttest non-equivalent control group design was conducted in SMAN 1 and SMAN 8 Yogyakarta, Indonesia during the academic year 2018/2019. A cluster sampling technique was used to select 3 eleventh grade classes of natural science from each school. The criterion referenced essay test was used to measure the students’ learning achievements and the data collected were analyzed using SPSS version 23. The results show that both PjBL and 5E learning instructional models were effective to improve the students’ ability to acquire new biological knowledge related to the human immune system. PjBL model was more effective than 5E learning cycle model in improving the students’ ability to acquire new biological knowledge related to the human immune system.